Exito de proyectos : identificación de factores críticos del éxito (CSF) de proyectos y criterios del éxito de proyectos para las empresas del sector de construcción colombiano (2016)
Project success has been one of the most studied topics within the academic world in many fields for the past several years. This Master's degree graduation project addresses the gap in current project management research by presenting the results of a quantitative study based on 63 responses to a 131 question electronic survey meant to identify the Critical Success Factors (CSF) that are most influential on the success of a project as measured by 32 indicators. The content of said survey was based on a bibliographic study of scholarly and professional articles published since 1986 with a special focus on the history of project management, the projectization of organizations, Critical Success Factors (CSF) and measurement of project success.